2014
DOI: 10.1007/s00259-014-2793-8
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT imaging and the oligometastatic prostate cancer patient: an opportunity for a curative approach with high-dose radiotherapy?

Abstract: Although not curative, androgen deprivation (AD) therapy is presently the first treatment option for patients with recurrent and/or metastatic prostate cancer [1]. Metastatic prostate cancer most frequently becomes resistant to continuous AD after an average treatment time of 2 -3 years [2]. Furthermore, long-term AD may induce substantial side effects in patients compromising general health status and quality of life including cognitive and sexual impairment, fatigue, cardiovascular dysfunction, metabolic syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These patients may be amenable to salvage surgical treatment with either a lymph node dissection or targeted radiotherapy to the nodal recurrence. Whilst a PSA >0.2 ng/mL is a common definition of biochemical recurrence, earlier detection of recurrence is desirable given the emerging field of oligometastatic treatment . Winter et al.…”
Section: Discussionmentioning
confidence: 99%
“…These patients may be amenable to salvage surgical treatment with either a lymph node dissection or targeted radiotherapy to the nodal recurrence. Whilst a PSA >0.2 ng/mL is a common definition of biochemical recurrence, earlier detection of recurrence is desirable given the emerging field of oligometastatic treatment . Winter et al.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the current study findings of higher TCPs associated with Plan 100-105Gy . It may be advantageous in terms of local tumor control to pursue both a high whole-prostate dose and a high boost differential, since a high boost dose at the expense of a lower whole prostate dose (< 70–75 Gy) has been associated with relatively high failure rates [39-42]. In contrast to the > 20 Gy differential boost dose of the current study, the average differential dose (PTV IDL –PTV prostate ) reported in a systematic review was 8 Gy (biologically effective dose 2 Gy per fraction, α/β = 3 Gy, range 3–35 Gy) and the most common rectal dose constraints used were V70Gy < 15–30% with D max of 76–80 Gy [8].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, multiple studies evaluating the use of stereotactic radiation or other focal therapy for the treatment of oligometastatic have relied heavily on PET/CT (with various radiotracers) due to a better selection of patients who are truly oligometastatic [38,39]. An early study evaluating the use of 11 C-choline PET/CT demonstrated that this approach could produce a useful single diagnostic exam in the evaluation of patients with moderate to high-risk prostate cancer with the potential of metastatic spread and can reliably rule out lymph node and distant metastases and establish eligibility for pelvic radiotherapy [40]. Another study found that the image-guided ablation of oligometastases identified by 11 C-choline PET/CT offered acceptable local tumor control rates and may allow for a delay of ADT initiation [41].…”
Section: Studies Integrating Pet Into Diagnosis and Treatment Of Olig...mentioning
confidence: 99%